2020
DOI: 10.1111/acer.14344
|View full text |Cite
|
Sign up to set email alerts
|

Brucine N‐Oxide Reduces Ethanol Intake and Preference in Alcohol‐Preferring Male Fawn‐Hooded Rats

Abstract: Background: Alcohol use disorder places a heavy burden on global public health systems and thus is in urgent need of improved pharmacotherapies. Previously, our group has demonstrated that 30 mg/kg of the indole alkaloid brucine significantly attenuates alcohol-drinking behavior; however, the high toxicity, poor water solubility, short half-life, and limited therapeutic window of brucine restrain its clinical application as an antialcoholism medication. We subsequently hypothesized that the oxide of brucine (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…CPP is a model used to study the conditioned reinforcing properties of drugs of abuse through the association of putative drug reward with neutral environment cues. 6,18 In this study, we investigated the role of Hsp70 in morphine CPP in male rats using the pharmacological interventions. In this study, we found that icv PES and KNK437 4) In their study, mice were treated with GGA (800 mg/kg/day) in an oral manner, whereas in our study, rats were injected with the pharmacological antagonists/inhibitors in an icv way.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…CPP is a model used to study the conditioned reinforcing properties of drugs of abuse through the association of putative drug reward with neutral environment cues. 6,18 In this study, we investigated the role of Hsp70 in morphine CPP in male rats using the pharmacological interventions. In this study, we found that icv PES and KNK437 4) In their study, mice were treated with GGA (800 mg/kg/day) in an oral manner, whereas in our study, rats were injected with the pharmacological antagonists/inhibitors in an icv way.…”
Section: Discussionmentioning
confidence: 99%
“…CPP is a model used to study the conditioned reinforcing properties of drugs of abuse through the association of putative drug reward with neutral environment cues 6,18 . In this study, we investigated the role of Hsp70 in morphine CPP in male rats using the pharmacological interventions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Single-housed P- and NP-rats (male, ~200 g) had continuous access to one bottle of 5% alcohol ( v / v ) and one bottle of water in their home cage for four consecutive weeks according to a two-bottle free choice (2-BC) paradigm [ 23 , 24 ]. The mass of drinking liquid (5% alcohol and water) was monitored every day, and the bottles were randomly replaced every day.…”
Section: Methodsmentioning
confidence: 99%